Best Practice in Swallowing Assessment in COVID-19 - Warner, Heather; Young, Nwanmegha (Dysphagia, 2022)
The COVID-19 pandemic has significantly altered the world as we know it. Service delivery for the instrumental evaluation of dysphagia in hospitalized patients has been significantly impacted. In many institutions, instrumental assessment was halted or eliminated from the clinical workflow, leaving clinicians without evidence-based gold standards to definitively evaluate swallowing function. The aim of this study was to describe the outcomes of an early, but measured return to the use of instrumental dysphagia assessment in hospitalized patients during the COVID-19 pandemic. Data was extracted via a retrospective medical record review on all patients on whom a swallowing consult was placed. Information on patient demographics, type of swallowing evaluation, and patient COVID status was recorded and analyzed. Statistics on staff COVID status were also obtained. Over the study period, a total of 4482 FEES evaluations and 758 MBS evaluations were completed. During this time, no staff members tested COVID-positive due to workplace exposure. Results strongly support the fact that a measured return to instrumental assessment of swallowing is an appropriate and reasonable clinical shift during the COVID-19 pandemic.
1 citations (Crossref) [2023-10-31]
Keywords: COVID; Deglutition; Dysphagia; FEES; Swallowing assessment; dept.cmd; peer-reviewed